Reforming Sharia Business Law in Indonesia: Reconstructing a Contemporary Legal Framework for Islamic Financial Integration - Achmad Jaka Santos Adiwijaya; Martin Roestamy; Abraham Yazdi Martin; Radif Khotamir Rusli; Ismail Sugardo (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2025)
Indonesia's ambition to become a global leader in Islamic finance is significantly hampered by a fragmented and sectoral Sharia business law structure. Despite substantial legislative progress, including the enactment of the Sharia Banking Law (Law No. 21 of 2008), the Financial Services Authority Law (Law No. 21 of 2011), and the Halal Product Assurance Law (Law No. 33 of 2014), regulatory power remains dispersed across various institutions and state agencies. This study employs a qualitative doctrinal legal research method, complemented by comparative and descriptive quantitative analysis, to examine Indonesia's current regulatory configuration against the backdrop of jurisdictions like Malaysia, Bahrain, the United Kingdom, and Brunei Darussalam. The findings reveal that overlapping jurisdictions, delayed implementation of fatwa-based rulings, and the absence of a unified Sharia governance framework have constrained the country's Islamic finance regulation. The paper proposes the establishment of an autonomous, comprehensive Sharia Financial Services Authority, the enactment of a professional Sharia Business Law Code harmonized with international standards, and the adoption of technology-based supervision. This contemporary legal reform is essential to ensure institutional consistency, strengthen legal certainty in Islamic finance, and advance public welfare (maslahah) through a fully integrated Islamic financial system in Indonesia.